Pemanfaatan Daun Kemangi Sebagai Bahan Tambahan Briket Anti Nyamuk Alami di Desa Bendiljati Wetan Tulungagung - Kartika Arum Wardani (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The Indonesian people need to be aware of the threat of Dengue Hemorrhagic Fever (DHF) in the rainy season this year. Indonesia is one of the endemic countries which has quite a large number of cases of dengue fever from 30 other endemic countries each year. DHF cases in Indonesia continue to increase in several provinces, including in Tulungagung Regency. One of the efforts of STIKes Karya Putra Bangsa is to provide community service programs to participate in local government activities in eradicating the Aedes aegypti mosquito that causes DHF. The program we carry out is counseling and coaching the manufacture of natural mosquito repellent briquettes from rice husks and additional dried basil leaves and other natural ingredients such as cloves and lemongrass. The target of this activity is the recitation mothers in Bendiljati Wetan village, Sumbergempol-Tulungagung sub-district. The results of this activity are that the entire community is enthusiastic and satisfied with this activity, 83% of participants are interested in making and trying again at home, and only 6.67% of participants are willing to do the briquette business while the rest prefer not.